Declining responsiveness at the establishment level: Sources and productivity implications - Russell W. Cooper; John C. Haltiwanger; Jonathan L. Willis (Federal Reserve Bank of Atlanta, 2024)
This paper studies competing sources of declining dynamism. Evidence shows that an important component of this decline is accounted for by the reduction in the response of employment to shocks in US establishments. Using a plant-level dynamic optimization problem as a framework for analysis, four potential reasons for this decline are studied: (i) a change in exogenous processes for profits, (ii) an increase in impatience, (iii) increased market power, and (iv) increasing adjustment costs. We identify and quantity the contribution of each of these factors building on a simulated method of moments estimation of our structural model. Our results indicate that the reduction in responsiveness largely reflects increased costs of employment adjustment. Changes in market power, as captured by changes in the curvature of the revenue function, play a minimal role. But, in the presence of rising adjustment costs, measured sales-weighted markups using the recently popular indirect production approach rise substantially, along with rising dispersion and skewness of such measured markups.
Keywords: E24; E32; J23; 330; declining dynamism; adjustment costs; employment